Change in climate and climate suitability of major taro [Colocasia esculenta (L.) schott] growing regions of India - G. Byju; Jinimol Raju; R. Shiny (JOURNAL OF ROOT CROPS, 2024)
Root and tuber crops such as taro [Colocasia esculenta (L.) schott] play a vital role in food security and livelihoods and yet neglected in climate change impact studies and large-scale crop improvement programs. This study attempts ensembled multi-model prediction of change in climate and climate suitability of taro in major taro growing regions of India by 2030 and 2050 under 4.5 and 8.5 representative concentration pathways (RCP). Climate, suitability (EcoCrop model) and suitability changes were analysed using Arc GIS 10.1 and Diva GIS 7.5. According to the study, under RCPs 4.5 and 8.5, the major taro growing regions will experience warming of the climate by 2030 and 2050. The mean temperature of major taro growing regions in 2030 will increase by 1.15- 1.49°C and 1.58 – 2.09°C for RCPs 4.5 and 8.5; and 1.35 - 1.70°C and 2.02 - 2.68°C for RCPs 4.5 and 8.5 in 2050. The precipitation in 2030 will increase by -2.01 – 82.07 mm and 2.84 - 128.02 mm for RCPs 4.5 and 8.5; and in 2050 it will change by 13.48 to 16.98 mm and 1.09 to 108.54 mm for RCPs 4.5 and 8.5. The climate suitability will change by -12.31 to 5.17% and -14.29 to 7.63% in 2030 for RCPs 4.5 and 8.5; and -18.26 to 6.57% and -24.1 to 9.39% for RCPs 4.5 and 8.5 in 2050.